International perspectives on the pedagogically innovative uses of technology - Kankaanranta, Marja (Human Technology, 2021)
The children of today grow up having information and communication technologies (ICTs) as essential and natural parts of their daily life. As they grow, they are expected to become active and self-directed members in their own local communities and also in the information society at large. Technology creates versatile possibilities for the acquisition and creation of information, for self-expression, and for communication and interaction with other people locally, nationally, and worldwide. Active participation in the information society presumes novel knowledge, skills, and work approaches from children and teachers alike.